First report of the parasitoid wasps, Microchelonus subcontractus and Bracon intercessor (Hym.: Braconidae), from Iran - A. Lozan; M. Basij; M. Mahmoudvand; H. Abbasipour (نامه انجمن حشره‌شناسی ایران, 2012)
This paper reports the occurrence of the hymenoterous parasitoids of the beet moth, Scrobipalpa ocellatella Boyd larvae in Iran for the first time. Two braconid species of Microchelonus subcontractus Abdinbekova and Bracon intercessor Nees were collected from the larvae of S. ocellatella in the sugar beet fields located in Ray, the southern district of Tehran. These parasitoids are belonging to the subfamilies Cheloninae and Braconinae, respectively.